The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1987
DOI: 10.2170/jjphysiol.37.601
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cold and immobilization stress on noradrenaline turnover in brown adipose tissue of rat.

Abstract: Noradrenaline (NA) turnover of the interscapular brown adipose tissue (BAT) was determined in order to evaluate a role of sympathetic NA of this tissue in an enhanced nonshivering thermogenesis which had been previously evidenced in the repetitively stressed rats by immobilization (daily 3-h immobilization for 4 weeks) and the coldacclimated ones (5°C, 4 weeks). The disappearance rate of NA from the BAT following blockade of NA synthesis with a-methyl p-tyrosine was adopted for estimation of NA turnover of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 13 publications
(16 reference statements)
3
6
0
Order By: Relevance
“…The brown fat is a major site of cold stress-induced nonshivering thermogenesis (44 ), and increased sympathetic activity is a major factor regulating thermogenesis in this tissue (45 ). Furthermore, cold exposure increases NA turnover of brown fat (46,47). In the present study, TH activity in brown fat was elevated significantly only after 5 days of continuously cold stress, but not by SART stress.…”
Section: Discussionsupporting
confidence: 43%
“…The brown fat is a major site of cold stress-induced nonshivering thermogenesis (44 ), and increased sympathetic activity is a major factor regulating thermogenesis in this tissue (45 ). Furthermore, cold exposure increases NA turnover of brown fat (46,47). In the present study, TH activity in brown fat was elevated significantly only after 5 days of continuously cold stress, but not by SART stress.…”
Section: Discussionsupporting
confidence: 43%
“…Regulation of UCP1 thermogenic function is mediated by tonic release of NE from the sympathetic nerve terminals that innervate BAT [4]. Immobilization increases sympathetic activity in BAT, as estimated by NE turnover rate [32]. In the present study, acute immobilization increased UCP1 function irrespective of repeated immobilization exposure.…”
Section: Discussionsupporting
confidence: 47%
“…We previously demonstrated that the BAT NE turnover rate was significantly higher in repeatedly immobilized rats than in naive rats when both groups were exposed to acute immobilization [32]. Glucocorticoids possess a powerful inhibitory effect on UCP1 function by attenuating SNS activity [33][34][35] and by directly suppressing UCP1 gene expression [17,20].…”
Section: Discussionmentioning
confidence: 99%
“…A negative stress for a rodent would be to be suspended by a hindlimb (Yamashita et al, 1995) or the tail (Lew et al, 2009), immobilized (Gao et al, 2003;Harris et al, 2006;Murazumi et al, 1987), or exposed to foot shock (McGregor et al, 1994) or social defeat (Lkhagvasuren et al, 2011). In all these cases, there are indications that at least the nerves to brown fat are activated; the sympathetic nerves to white adipose tissue are also most likely activated, and browning may thus be induced.…”
Section: Stress: Positive and Negativementioning
confidence: 99%